Primary and secondary organic aerosols in urban air masses intercepted at a rural site - Liggio, John; Li, Shao-Meng; Vlasenko, Alexander; Sjostedt, Steve; Chang, Rachel; Shantz, Nicole; Abbatt, Jonathan; Slowik, J. G.; Bottenheim, J. W.; Brickell, P. C.; Stroud, C.; Leaitch, W. Richard (JOURNAL OF GEOPHYSICAL RESEARCH-ATMOSPHERES, 2010)
Measurements made at a rural site in central Ontario during May-June 2007 are used to investigate the composition of organic aerosol (OA) downwind of an urban region. Observations of aerosol organic carbon and oxygen containing fragments from a high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS) are combined with toluene to benzene ratios to estimate the relative importance of secondary organic aerosol (SOA) and primary organic aerosol (POA) to the total OA at the site during periods of significant urban influence. We estimate that SOA formed within 1-2 days of the anthropogenic source regions was 40-50% of the measured OA and that POA was 5-16% of the OA. The remaining 35-45% of the OA is assumed to have been present in the aerosol upwind of the source regions prior to entering the study domain as defined by trajectories and estimates of the potential photochemical aging time. The apportionment results were also compared to that of positive matrix factorization analysis. In addition, the measurements of the molar oxygen to carbon ratio (O/C) in the OA demonstrates that SOA becomes progressively more oxygenated with increasing photochemical age and at low total OA mass.